Modification of spatial domain algorithms for apertureless light propagation - Brenner, Karl-Heinz; Mehrabkhani, Soheil (Applied optics, 2017)
Light propagation algorithms in the spatial domain hold an implicit assumption that the calculation region represents a virtual aperture, i.e., the amplitude outside of the calculation region is zero. With typically bright objects on a dark background, this assumption is legitimate and the calculation is correct. With dark objects on a bright background, however, the assumption is violated and the calculation result is dominated by diffraction effects at a virtual aperture. This virtual aperture diffraction is especially a problem for pure phase elements, because the amplitude in and beyond the calculation region is a constant one. In this paper, we explain the background of the problem and present a general and effective method to remove this problem.